2019
DOI: 10.26832/24566632.2019.040402
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the effects of human urine on phenology and some cultivar coefficients of Cowpea (Vigna unguicalata. L. Walp) using the DSSAT-CROPGRO model

Abstract: The DSSAT-CROPGRO model was used to characterize phenology and cultivar coefficients of cowpea treated with diluted human urine (equivalent to 60 kg-N/ha), simulated under ten irrigation schedules for a 5 year production period in Juba County of Central Equatoria State, South Sudan. Two treatments (T 0) without urine and (T 1) with human urine dilution during the growing season of 2016 were used and, 5-years model simulations on the grain number/m², LAI, canopy height (m) and pod number/m² compared. Irrigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Such a high N on the four-fold N (uptake) by T 1 than under T 0 , would suggest the significance of fertigation as well as the role of N in enhancing cowpea nodulation, which in turn must have facilitated increase in N (uptake) . Although cowpea plants symbiotically fix atmospheric nitrogen, the additional application of 60 kg ha -1 of organic nitrogen fertilizer enhanced a three-fold N (uptake) and so positively affected cowpea phenology and yield significantly (Lomeling and Huria, 2019). The findings of (Xia et al, 2017) showed that low concentrations of nitrogen (<50 mg/L) added to soybean plants tended to increase nodulation while higher concentrations (>50 mg/L) had an inhibitory effect.…”
Section: Nitrogen Dynamics and Balancementioning
confidence: 97%
See 1 more Smart Citation
“…Such a high N on the four-fold N (uptake) by T 1 than under T 0 , would suggest the significance of fertigation as well as the role of N in enhancing cowpea nodulation, which in turn must have facilitated increase in N (uptake) . Although cowpea plants symbiotically fix atmospheric nitrogen, the additional application of 60 kg ha -1 of organic nitrogen fertilizer enhanced a three-fold N (uptake) and so positively affected cowpea phenology and yield significantly (Lomeling and Huria, 2019). The findings of (Xia et al, 2017) showed that low concentrations of nitrogen (<50 mg/L) added to soybean plants tended to increase nodulation while higher concentrations (>50 mg/L) had an inhibitory effect.…”
Section: Nitrogen Dynamics and Balancementioning
confidence: 97%
“…The CROPGRO model satisfactorily simulated the positive effect of human urine on cowpea yield. This positive effect is particularly attributable to the role of macro-and micro elements contained in the urine (Lomeling and Huria, 2019).…”
Section: Biophysical Analysis: Grain Yield and Fertigationmentioning
confidence: 99%